Particle size effect on caking in sucrose : a thesis presented in partial fulfilment of the requirements for the degree of Masters in Chemical Technology at Massey University - Clarke, Rebecca (Massey University, 2005)
Caking, and the associated loss of flowability, have for a long time been a problem in the sugar industry, causing difficulties during conveying and making the product unacceptable to consumers. There are many factors that are thought to contribute to this problem, including relative humidity, compaction and packing of the crystals, and particle size. In order to determine if particle size did have an effect, a series of samples containing different sized crystals, and different proportions of fine crystals were created. These samples then had their water vapour sorption isotherms measured by equilibrating samples over saturated salt solutions. Caking tests were also carried out using the friability test and the blowtest. No significant difference was found on either the isotherms or the friability test. The blowtest, however, was found to be much more sensitive to the small differences in caking occurring between samples. It was found that only fines less than 150 µm had any effect on caking, and even then, only when they were present in large quantities. In addition, the smaller the particles, the smaller the amount required for caking to occur. For example, the critical water activity for standard sugar was found to be 0.61. For a sample of 100% 212-315 µm particles this decreases to 0.55 and for a sample of 0-75 µm this decreases even further, to 0.22. No additional effect was found to be caused by crystal damage, over and above the effect of decreased particle size. It is proposed this increase in caking in fine particles is due to capillary condensation. The smaller the crystals, or the greater the proportion of fines small crystals present, the more contact points between particles. Between each of these contact points capillary condensation can occur, which means more moisture can be absorbed at a lower water activity, therefore, the amount of water needed for caking to occur is also reached at a lower water activity. This effect is very small, and neither the isotherms nor the friability test was able to detect these changes, but the blowtester was able to. Some of these fine crystals will originate in the crystallisation process, however many of the fine crystals are a product of attrition. It was found that this was a problem when sugar was conveyed using a screw conveyor, but not when a redler chain conveyor was used. In addition, there were no differences found in the amount of attrition occurring when conveyors are run at less than full loads. It is recommended that in future construction and modification of the plant, chain redlers be considered rather than screw conveyors.
Keywords: Sucrose -- Storage